Santri Entrepreneurship Education in the Market Day Program at Kuningan Pembangunan Islamic Boarding School - Abdullah, Fadli Daud; Ludfi, Ahmad; Taqiyuddin; Fatihah, Imroatul; Wiwaha, Syahid Mujahid (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
This study investigates how the Kuningan Pembangunan Islamic Boarding School effectively developed entrepreneurship among its students in 2022, from May to June. It delves into the background of the school, which houses various business units like food industry and services. Employing qualitative methods, the research engages leaders, entrepreneurship facilitators, educators, and students as subjects. Data collection encompasses observation, interviews, and documentation. The findings revealed meticulous planning as the backbone of entrepreneurial spirit cultivation at the school. Leaders, facilitators, educators, and students collaborate in planning, covering talent screening, class organization, scheduling, certification, and bazaar arrangements. Market Day emerged as a tangible manifestation of the entrepreneurship education program, offering both theoretical learning and practical engagement. Regular evaluations ensure students' active participation in learning and business management. The study emphasized the significance of such programs in nurturing competitive individuals who can contribute to societal and economic development. It also deepens the pivotal role of Islamic Boarding Schools in fostering entrepreneurial skills among students, offering insights valuable for designing effective entrepreneurship education programs in other educational institutions.